PERGANTIAN AUDITOR SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE PADA AUDIT DELAY - Brawida Uthama, Gede Oka; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
The purpose of this study examines the effect of firm size, profitability, leverage audit delay and change of auditor as moderating profitability and leverage. This study was performed on companies listed in the Indonesia Stock Exchange in 2012, which used a sample of 132 companies using a quantitative approach in the form of associative. Methods of data collection with a non-participant observation and analysis techniques used are Moderate Regression Analysis. Results showed that all results obtained with the hypothesis.
Keywords: change of auditors, company size, profitability, leverage, audit delay